The detection of intracranial calcifications by MR. - Oot, R F; New, P F; Pile-Spellman, J; Rosen, B R; Shoukimas, G M; Davis, K R (American Journal of Neuroradiology, 1986)
Twenty patients in whom CT had unequivocally demonstrated the presence of calcification in a diversity of lesions and who had undergone MR, performed at 0.6 T and with standard T1- and T2-weighted pulse sequences, were retrospectively studied to determine the MR signal-intensity characteristics of the calcifications and to assess the ability of MR to detect the presence of this abnormality. CT proved superior to MR in detecting and characterizing calcification. In seven of 20 cases, the apparent extent of calcification was equal by both imaging techniques, and in 13 of the 20 cases, CT showed more extensive abnormality. In five of the 20 cases, the calcifications were seen by MR as regions of profoundly reduced signal intensity, approximately equal to cortical bone, in all pulse sequences. In 12 of the 20 cases, the signal intensity was profoundly reduced in one or more, but not all, pulse sequences. T2-weighted pulse sequences were most sensitive in detecting calcification of signal void. Reviewed without knowledge of the CT findings, the MR images were interpreted as definitely indicative of the presence of calcification in three of the 20 cases. In seven of the 20 cases, the MR images raised the possibility of calcification but were less definitive than the CT findings. In 10 of the 20 cases, MR was judged indeterminate for the presence of calcification.